Comparison of MCNP modeling against empirical data for the measurement of gamma fields due to actinide oxides in a glovebox - Adams, David Wright, author; Brandl, Alexander, advisor; Johnson, Thomas E., committee member; Lindsay, James E., committee member (Colorado State University. Libraries, 2012)
Los Alamos National Laboratory (LANL) is a facility that conducts research in the fields of global security, astrophysics, nuclear energy, and materials science. At Technical Area 55 (TA-55) actinide oxides used for experimental nuclear fuel research are placed in gloveboxes to be manipulated by glovebox operators. The actinide oxides are radioactive and emit gamma rays which impact the glovebox operator. Although proper precautions protect workers from unnecessary dose, the measurement and characterization of the gamma fields are useful in deciding if multiple dosimetry may be necessary as per standards at the lab and national standards. Experimental measurements were made by radiation protection personnel of TA-55 at the glovebox containing different actinide oxides. Thermoluminescent dosimeters (TLDs) were utilized to determine the dose to workers at the glovebox. A lead apron covered some of the TLDs while others were left unshielded to simulate shielded and unshielded portions of the body. Monte Carlo N-Particle Code Version 5 (MCNP5) was used to model and simulate the experimental setup at TA-55 to determine the efficacy of the lead apron and to determine the spatiality of the dose distribution as required to determine whether multiple dosimetry is necessary or not. Multiple dosimetry was found to not be required given that the TLD's are worn on the chest, at the location of highest dose.
Keywords: actinide oxide; Monte Carlo; MCNP; glovebox; dosimetry